Researching Collocations in Another Language - Barfield, Andy. author. aut Link
XIX, 273 p.
Keywords: This volume brings together original research in the four areas of L2 collocation learner corpora, L2 collocation lexicographic and classroom materials, L2 collocation knowledge assessment, and L2 collocation learner processes. Each area is covered by three research chapters and a dedicated commentary chapter by experts in the field.